مساهمة البرامج التكوينية في تجويد معايير الكفايات المهنية لأساتذة المرحلة الابتدائية - شالوش,سامية; بشتة,حنان (University of Eloued جامعة الوادي, 2024)
ملخص : هدفت الدراسة إلى التعرف على مساهمة البرامج التكوينية في تجويد معايير الكفايات المهنية لأساتذة المرحلة الابتدائية، استخدمت الدراسة المنهج الوصفي، وتكونت عينة الدراسة من(130)أستاذ وأستاذة في بعض ابتدائيات ولاية جيجل حيث طبقت عليهم استبانة مكونة من(28) بندا موزعة على ثلاث محاور وهي: مساهمة البرامج التكوينية في تجويد معايير الكفايات التدريسية، مساهمة البرامج التكوينية في تجويد معايير الكفايات الإدارية الصفية، مساهمة البرامج التكوينية في تجويد معايير الكفايات التعليمية الإلكترونية، ومساهمة البرامج التكوينية في تجويد معايير الكفايات اللغوية. وقد كشفت النتائج أن مساهمة البرامج التكوينية في تجويد معايير الكفايات المهنية حسب أساتذة المرحلة الابتدائية كانت بدرجة متوسطة، كما جاءت نتائج محاور الدراسة كالآتي: الكفايات التعليمة الإلكترونية بدرجة مرتفعة، تليها الكفايات التدريسة بدرجة مرتفعة، تليها الكفايات الإدارية الصفية بدرجة متوسطة وفي الأخير الكفايات اللغوية بدرجة متوسطة. وقد قدمت الدراسة عددا من التوصيات والمقترحات. Abstract : The studyaimed to identify the contribution of the formative programs in improving the standards of professionalcompetencies for primaryschoolteachers. The studyused the descriptive approach.The studysampleconsisted of(130) male and femaleteachers in some of the elementaryschools in Jijel state, where a questionnaire consisting of(28) items distributed over threeThey are: the contribution of the training programs to improve the standards of teachingcompetencies, the contribution of the training programs to the improvement of the standards of classroom administrative competencies, the contribution of the training programs to the improvement of the standards of electroniceducationalcompetencies, and the contribution of the training programs to the improvement of the standards of linguisticcompetencies. The resultsrevealedthat the contribution of the training programs to improving the standards of professionalcompetenciesaccording to the teachers of the primary stage wasat a medium degree, and the results of the study axes were as follows: the e-learning competenciesat a highdegree, followed by the teachingcompetenciesat a highdegree, followed by the classroom administrative competenciesat a medium degree, and finally the linguisticcompetenciesat adegree Medium The studypresented a number of recommendations and proposals
دراسة ميدانية ببعض ابتدائيات مدينة جيجل
Keywords: برامج تكوينية; معايير جودة الكفايات المهنية; أساتذة المرحلة الإبتدائية; formative programs; quality standards for professionalcompetencies; primaryschoolteachers